Composition of matter for converting biochar into low surface area graphite
By combining biochar, metal compounds, liquids and additive preparations and high-temperature heat treatment, the problem of difficult to effectively use renewable carbon material sources to produce graphite in the prior art is solved, and graphite production with high conversion and low surface area is achieved, and it is suitable for lithium-ion batteries and other fields.
Patent Information
- Application Number
- CN202380052778.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-29
- Filing Date
- 2023-07-28
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art is difficult to effectively utilize renewable carbon material sources to produce graphite economically and sustainably, especially in the case of increasing demand in areas such as lithium-ion batteries.
By combining biochar, metal compounds, liquids and additive formulations, a substance composition is formed and heat treated at high temperatures to convert it into a graphite material with a low surface area.
High conversion rate graphite production is achieved, with the specific surface area of graphite less than 50m2/g, and the graphite material characteristics of different applications can be adapted to the proportion of components.
Smart Images

Figure CN119698392A_ABST
Abstract
Description
Field of the Invention
[0001] The present invention relates to a composition of matter suitable for converting biochar into graphite with low surface area suitable for a wide range of applications. The composition of matter comprises biochar, a metal compound, a liquid and an additive formulation selected from one or more of the following: a surfactant, a binder, a dispersant, a rheology modifier, a wetting agent, an anti-foaming agent or any combination thereof. Background Art
[0002] Graphite is either synthetic or obtained from natural deposits. Some carbon materials such as coke and mesophase pitch can be converted to graphite simply by heating, and such materials are called graphitizable. Rosalind Franklin [1] describes graphitizable carbons as those that can be converted to crystalline graphite by heating to 3000 degrees Celsius. On the other hand, other carbon materials cannot be converted to graphite simply by heating and do not spontaneously convert to graphite at any temperature and are therefore described as non-graphitizable carbon materials.
[0003] Before heat treatment, the physical properties of these two types of carbon are very similar. Both materials are generally derived from hydrocarbons and initially contain other elements such as hydrogen, oxygen, nitrogen and sulfur. Graphitized carbons tend to be aromatic in structure, while non-graphitized carbons tend to be aliphatic. Therefore, a key difference between the two is the H:C ratio, with aromatics having a lower H:C ratio. Only upon heating are the heteroelements removed and only the structure of the carbon left behind is created. The key step in the formation of high-quality synthetically derived graphite is the polycondensation reaction that forms large polycyclic aromatic hydrocarbons (PAH's). When heated the PAH's arrange to form a graphite structure, and in some non-graphitized carbons this structural arrangement can be stopped by cross-linking. However, in many other cases, no PAH's are formed at all after heat treatment, resulting in only very small graphite crystallites when heated to 3000 degrees Celsius.
[0004] The demand for graphite has increased significantly due to the need for graphite in lithium-ion batteries. The mining of natural graphite resources has significant environmental impacts. And the production of synthetic graphite requires crude oil and other non-renewable resources. New methods for graphitization using renewable sources of carbon materials are needed to produce graphite sustainably and economically. One such source is renewable biomass, which forms carbonaceous char when heated, which is a non-graphitizable form of carbon. Summary of the invention
[0005] The present disclosure provides a composition of matter, which includes biochar, a metal compound, a liquid in which the metal compound has a minimum solubility, and an additive formulation selected from one or more of the following: a surfactant, a binder, a dispersant, a rheology modifier, a wetting agent, an anti-foaming agent, or any combination thereof. This particle, wet slurry mixture has a series of unique properties, which enables it to produce a graphite material with a low surface area at a high conversion rate when thermally treated. By changing the amount of the components, the graphite material properties can be adjusted to adapt to a specific application. This cannot be easily achieved using dissolved metal compounds because their solubility in a given liquid is limited, and it is practically infeasible to control the size of the precipitated particles beyond a limited range. A method for producing this composition of matter is also disclosed.
[0006] In a first aspect, a composition of matter is provided, comprising a mixture of biochar, a metal compound, a liquid, and an additive formulation, wherein the mixture comprises (a) about 1 to about 90 weight percent of the biochar, (b) about 2 to about 90 weight percent of the metal compound, (c) about 0.001 to about 83 weight percent of the liquid, and (d) about 0.001 to about 5 weight percent of the additive formulation, wherein the additive formulation is selected from one or more of the following: a surfactant, a binder, a dispersant, a rheology modifier, a wetting agent, an anti-foaming agent, or any combination thereof.
[0007] It should be understood that any weight percentages of the four components may be selected from these specified ranges as long as the sum totals 100%.
[0008] In one embodiment, the liquid is selected to ensure that when the composition is used, the solubility of the metal compound in the liquid is minimal. In a further embodiment, the liquid is water.
[0009] In one embodiment, the metal compound comprises a transition metal. In a further embodiment, the transition metal is selected from chromium, zirconium, molybdenum, ruthenium, rhodium, palladium, silver, cadmium, zinc, copper, nickel, cobalt, iron, manganese, chromium, vanadium or any combination thereof.
[0010] In one embodiment, any non-metallic portion of the metal compound may alternatively be derived from the use of any inorganic acid to generate salts, such as fluoride salts, chloride salts, sulfates, nitrates, phosphates, carbonates, etc. Alternatively, organic acids may generate organic salts. During thermal treatment, most of these inorganic and organic compounds will undergo decomposition to form metal oxides, so they may also be used indirectly. Depending on the selected starting metal compound, other intermediate compounds may also be formed.
[0011] In one embodiment, the metal compound is a transition metal oxide. In a further embodiment, the transition metal oxide is selected from oxides of iron, copper, nickel, manganese, vanadium, tin, chromium, zinc, titanium and cobalt, or any combination thereof.
[0012] In one embodiment, the mixture is dried and comprises, on a dry wt / wt basis, (a) between about 9.5 and about 90 weight percent of the metal compound, (b) between about 0.001 and about 5 weight percent of the additive formulation, and (c) between about 5 and about 90.5 weight percent of the biochar.
[0013] In one embodiment, the mixture is dried and comprises, on a dry wt / wt basis, (a) between about 19 and about 82 weight percent of the metal compound, (b) between about 0.001 and about 5 weight percent of the additive formulation, and (c) between about 13 and about 81 weight percent of the biochar. Any weight percent of the three components may be selected from these specified ranges as long as the sum totals 100%.
[0014] In one embodiment, the metal compound is a metal oxide.
[0015] In one embodiment, the metal oxide is a transition metal oxide.
[0016] In one embodiment, the transition metal oxide is selected from oxides of iron, copper, nickel, manganese, vanadium, tin, chromium, zinc, titanium and cobalt, or any combination thereof.
[0017] In one embodiment, the metal oxide is iron oxide.
[0018] In one embodiment, the mixture is dried and comprises, on a dry wt / wt basis, (a) between about 9.5 and about 80 weight percent iron oxide, (b) between about 0.001 and about 5 weight percent additive formulation, and (c) between about 20 and about 90.5 weight percent biochar, wherein the biochar has a fixed carbon content of about 70%. Any weight percent of the three components may be selected from these specified ranges as long as the sum totals 100%.
[0019] In one embodiment, the mixture is dried and comprises, on a dry wt / wt basis, (a) between about 19 and about 67 weight percent iron oxide, (b) between about 0.001 and about 5 weight percent additive formulation, and (c) between about 33 and about 81 weight percent biochar, wherein the biochar has a fixed carbon content of at least 70%. Any weight percent of the three components may be selected from these specified ranges as long as the sum totals 100%.
[0020] In one embodiment, the biochar is produced by thermally treating woody biomass.
[0021] In one embodiment, the biochar in the mixture is in particulate form.
[0022] In one embodiment, the biochar has an initial particle size of less than about 50 mm.
[0023] In one embodiment, the metal compound in the mixture is in particulate form.
[0024] In one embodiment, the metal compound and the biochar are both in particulate form.
[0025] In one embodiment, the primary particle size of the metal compound is less than about 5 mm.
[0026] In one embodiment, the biochar has an initial particle size of less than about 50 mm and the metal compound has an initial particle size of less than about 5 mm.
[0027] In one embodiment, the biochar has a particle size of less than about 800 microns.
[0028] In one embodiment, the biochar has a particle size of less than about 500 microns.
[0029] In one embodiment, the metal compound has a particle size of less than about 100 microns.
[0030] In one embodiment, the metal compound has a particle size of less than about 75 microns.
[0031] In one embodiment, the additive formulation includes two or more of a surfactant, a binder, a dispersant, a rheology modifier, a wetting agent, an anti-foaming agent, or any combination thereof. The additive must be selected based on the selected metal compound and the selected liquid in order to achieve suitable properties of the mixture in the selected processing step. In one embodiment, the selected metal compound may tend to agglomerate, in which case a suitable liquid-solid surfactant is required, in other embodiments, the biochar or metal compound is not easily wetted by the liquid, in which case a wetting agent must be added to achieve a uniform slurry mixture. In certain embodiments, it may be necessary to pump the slurry from one container to another, in which case a rheology modifier may be required to achieve a suitable viscosity, in other embodiments, the selected liquid may cause foaming during the slurry mixing process, so an anti-foaming agent will be required.
[0032] In one embodiment, the additive formulation includes one or more additives selected from the group consisting of: AEROSOL C-61, AG 6202, ALCOSPERSE 175, ALMIPAL P, Aminoethyl Ethanolamine, Ammonium Fluoride, AMMONYX M, Aquatreat BW30, Arkopal, Armid O. Aziridine, Polyisocyanates, Bronidox, BTBAB-90, BTBAC-50, Bteac-50, BTMAC-50, BTMAH-40, Styrene-butadiene binder, Styrene-butadiene binder, Butyl Stearate, Calcium Stearate, Dodecandioic acid, ENORDET, Ethoduomeen T / 25, EURAMAAT, EUR-AMID, EURANAAT, EURASOL, EUROGLYC, EUROQUAT, EUROWET, EUROXIDE, EXOdis PC30, FOAMASTER MO 2133, Heliogen BlueD 7079, Lauryl Alcohol, Lipal MSC, Lipal NTD, Magna MERPOL SE, NANSA, Oleamid, Oleic acid, Pasatell M-182 (2-798), PEG-400, Pentaerythritol Oleate, POIZ 520, POIZ 530, Polyamides, Polyesters, POLYFON H, Polyglycols, Polymerizable Additives, Potassium Soyate, Quickpearl PK3, REWOCID DU185SE, Rewopol SB L 203, ROKAmer 1010 / 50, SDS, Sico 50BC, Sidos 70, Sodium dodecyl benzene sulphonate, Sodium N-hexadecanoyl-L-alaninate, Sodium silicate, Sorbitan Mono Oleate, Sorbitan Monopalmitate, Steamcare B12, Stearyl Chloride, SugaDet APG-10, Sulfoccinate LSS, Sulphated Butyl Oleate, SURFACARE O ACID、TBAH-40、TBAHS-50、 DDM, TLMAC-30, TMAC-100ARQUAD 41-100, Tomamine Amphoteric 12, Triethanolamine, Triethylbenzylammonium Chloride, Tween 80, UFACID K, YB-0100, YB-150, YB-191, YB-2000, YB-904, YBASD-200, or any combination thereof.
[0033] In another aspect, there is provided a method of heat treating a composition as defined above to a temperature above the reduction temperature of the metal compound, thereby reducing it to the elemental metal or alloy and converting the amorphous biochar carbon to crystalline graphitic carbon.
[0034] In one embodiment, the conversion rate of amorphous carbon formed by thermally treating the mixture to crystalline graphite is greater than about 50%.
[0035] In one embodiment, the conversion to graphite is greater than about 75%.
[0036] In one embodiment, the crystalline graphite formed by heat treating the mixture has a crystallinity greater than about 90%.
[0037] In one embodiment, the crystalline graphite has a degree of crystallinity greater than about 95%.
[0038] In one embodiment, the graphite formed by heat treating the composition of matter defined above has a specific surface area of less than about 50 m 2 / g.
[0039] In one embodiment, the graphite has a specific surface area of less than about 30 m 2 / g.
[0040] In one embodiment, the method comprises the following steps:
[0041] i) thermally treating the biomass in particle form at a temperature of about 200 to about 1000 degrees Celsius under inert conditions to form a particle biochar;
[0042] ii) grinding the biochar to obtain a particle size of less than about 800 microns, more preferably less than 500 microns;
[0043] iii) milling a suitable metal compound to obtain a particle size of less than about 100 microns, more preferably less than 75 microns:
[0044] iv) combining the obtained biochar with the metal compound, liquid and additive formulation; and
[0045] v) heating the mixture to about 400 to about 3000 degrees Celsius under inert conditions to produce graphite carbon.
[0046] In one embodiment, the biomass is thermally treated in water in a hydrothermal step to produce biochar.
[0047] In one embodiment, the biomass is thermally treated under inert conditions in a dry pyrolysis step to produce biochar.
[0048] In one embodiment, the biomass is forestry residues.
[0049] In one embodiment, the forestry residue is sawdust.
[0050] In one embodiment, the biomass is lignocellulosic biomass or a lignin derivative.
[0051] In one embodiment, the biomass is wood chips or any other wood-based material.
[0052] In one embodiment, the liquid is water.
[0053] In one embodiment, the liquid and metal compound are selected to ensure that, in use, the solubility of the metal compound in the liquid is minimal.
[0054] In one embodiment, in step iv), the metal compound is combined with the biochar by wet blending together with an additive formulation in a mixer.
[0055] In one embodiment, in step iv), the metal compound is combined with the biochar by wet grinding in a mill together with an additive formulation.
[0056] In one embodiment, in step iv), the metal compound in water is combined with an additive formulation to produce a particulate metal compound slurry by using a mixer to form a particulate slurry in water.
[0057] In one embodiment, the additive formulation for the particulate metal compound slurry includes a surfactant, a binder, a dispersant, a rheology modifier, a wetting agent, an anti-foaming agent, or any combination thereof.
[0058] In one embodiment, in step iv), the biochar in water is combined with an additive formulation to produce a slurry of particulate biochar by using a mixer to form a slurry of particulates in water.
[0059] In one embodiment, the additive formulation for the particulate biochar slurry further includes a surfactant, a binder, a dispersant, a rheology modifier, a wetting agent, an anti-foaming agent, or any combination thereof.
[0060] In one embodiment, the particulate metal compound slurry is combined with the particulate biochar slurry and then blended together in a mixer.
[0061] In one embodiment, the mixture obtained in step (iv) is heated in step (v) to about 400 to about 3000 degrees Celsius using a controlled atmosphere oven, furnace or other heating device under inert conditions to produce graphite carbon, provided that the heat treatment temperature must be above the reduction temperature of the selected metal compound to ensure that it is reduced to the elemental metal or alloy state.
[0062] In one embodiment, the metal compound is a metal oxide.
[0063] In one embodiment, the metal oxide is a transition metal oxide.
[0064] In one embodiment, the transition metal oxide is selected from oxides of iron, copper, nickel, manganese, vanadium, tin, chromium, zinc, titanium and cobalt, or any combination thereof.
[0065] The foregoing and other aspects or advantages of the present invention will be apparent to those skilled in the art through use of the detailed description, images, analytical results, and performance test results provided in this specification. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 An image of a microwave heater used to produce the graphite samples described in this specification is shown.
[0067] Figure 2 a shows an image of a sample crucible placed in a microwave heater.
[0068] Figure 2 b shows an image of the sample crucible at high temperature.
[0069] Figure 3 The XRD diffraction pattern of the graphite sample produced in Example 1 is shown.
[0070] Figure 4 The XRD diffraction pattern of the graphite sample produced in Example 2 is shown.
[0071] Figure 5 The XRD diffraction pattern of the graphite sample produced in Example 3 is shown.
[0072] Figure 6 is a process diagram showing the overall conversion of biomass to graphite anode powder for lithium-ion batteries. DETAILED DESCRIPTION
[0073] The following description sets forth many exemplary configurations, parameters, etc. However, it should be appreciated that such description is not intended to limit the scope of the invention, but is provided as a description of exemplary embodiments.
[0074] All references, including patents and patent applications, cited in this specification are incorporated herein by reference. No admission is made that any reference constitutes prior art, nor does the discussion of any reference constitute an admission that that reference forms part of the common general knowledge in the art in New Zealand or any other country.
[0075] definition
[0076] In each instance herein, in the specification, embodiments, examples and claims, the terms "include", "comprising", etc. should be interpreted broadly and without limitation. Therefore, unless the context clearly requires otherwise, throughout the specification and claims, the words "comprise", "comprising", etc. should be interpreted in an inclusive sense rather than an exclusive sense, that is, in the sense of "including but not limited to".
[0077] As used herein, the articles "a" and "an" are used to refer to one or to more than one (ie, to at least one) of the grammatical object of the article. For example, "an element" may mean one element or more than one element.
[0078] The term "about" or "approximately" is used to indicate a wider range centered on a given value, and unless the context clearly indicates otherwise, it implies a wider range around the least significant digit, such as "about 1.1" implies a range from 1.0 to 1.2. If the least significant digit is unclear, the term "about" implies twice, for example, "about X" implies a value in the range of 0.5X to 2X, for example, about 100 implies a value in the range of 50 to 200. In addition, all ranges disclosed herein should be understood to include any and all subranges contained therein. For example, a range of "less than 10" may include any and all subranges between (and including) a minimum value of zero and a maximum value of 10, that is, any and all subranges (e.g., 1 to 4) having a minimum value equal to or greater than zero and a maximum value equal to or less than 10.
[0079] Unless otherwise defined, scientific and technical terms and nomenclature used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present disclosure belongs.
[0080] Although the numerical ranges and parameters listed in the broad range are approximate, the numerical values listed in the specific non-limiting examples are reported as precisely as possible. However, any numerical value inherently contains certain errors, which are necessarily caused by the standard deviation found in its respective testing measurements at the time of this writing. In addition, unless otherwise clear from the context, the numerical values presented herein have an implicit precision given by the first significant digit. Therefore, the value 1.105 implies a value from 1.0 to 1.2, while 1.105x10 2 The given value of 110.5 implies values from 100 to 120.
[0081] As used herein, the terms "biochar" or "carbonaceous char" or "char" are used interchangeably to refer to a material obtained by thermal decomposition of a carbonaceous material in an inert atmosphere.
[0082] As used herein, the terms "metal compound" or "metallic compound" are used interchangeably, and these terms refer to an organic or inorganic material containing a transition or non-transition metal, such as, but not limited to, chromium, zirconium, molybdenum, ruthenium, rhodium, palladium, silver, cadmium, zinc, copper, nickel, cobalt, iron, manganese, vanadium, sodium, magnesium, potassium, calcium, tin, or lead.
[0083] As used herein, the term "minimum solubility," when used in relation to a metal compound, means that less than about 0.1 g of the metal compound will dissolve in about 100 ml of a selected liquid at a neutral pH of 7.
[0084] As used herein, the term "amorphous" refers to a material that has no long-range or short-range structural order, as opposed to a crystal that has an arrangement of atoms in the form of a regular lattice, consisting of repeating, defined unit cells.
[0085] As used herein, the term "allotrope" means materials having the same elemental composition, such as, for example, pure carbon, but having different forms or atomic configurations, for example, diamond and graphite or amorphous biochar / char and graphite.
[0086] As used herein, the term "thermal treatment" means any thermal treatment process applied to biomass at a temperature sufficient to produce biochar, including hydrothermal and dry pyrolysis.
[0087] As used herein, the term "liquid" means a fluid in a liquid phase, such as but not limited to water.
[0088] As used herein, the term "water" means water sources, including low-quality water sources such as salt water, brine, or wastewater.
[0089] As used herein, the term "additive formulation" means an agent selected from one or more of the following: a surfactant, a binder, a dispersant, a rheology modifier, a wetting agent, an anti-foaming agent, or any combination thereof. Alternatively, an "additive formulation" may refer to a formulation comprising one or more agents selected from one or more of the following: a surfactant, a binder, a dispersant, a rheology modifier, a wetting agent, an anti-foaming agent, or any combination thereof. It should be understood that the additive formulation may include any number of combinations of surfactants, binders, dispersants, rheology modifiers, wetting agents, and / or anti-foaming agents. For example, as shown in Table 1, the additive formulation may include at least one binder and at least one surfactant. Alternatively, the additive formulation may include any combination of three or more, four or more, or five or more of surfactants, binders, dispersants, rheology modifiers, wetting agents, and / or anti-foaming agents. In addition, it should be understood that a single agent may have a multifunctional effect. For example, a single agent may act as a surfactant and a wetting agent. The additive formulation may optionally include one or more additional agents, such as, but not limited to, one or more carriers, solvents, or combinations thereof.
[0090] Table 1. Exemplary additive formulations comprising possible combinations of at least agent a and at least agent b
[0091]
[0092] Composite of biochar, metal compound, liquid and additive preparation
[0093] The material composition described in this specification includes a mixture of biochar, insoluble metal compounds, liquids and additive preparations. Biochar is generally derived from the pyrolysis of woody biomass. The metal compounds generally include transition metals. The liquid is generally water. The additive preparation includes a single or multifunctional mixture of one or more components selected from the following: surfactants, binders, rheology modifiers, dispersants, wetting agents, anti-foaming agents or any combination thereof. In order to produce the target mixture, the components are mixed or milled together, or milled separately and then combined. Then, in order to convert the mixture into graphite, the mixture can be subjected to a heat treatment procedure at a temperature between 400 and 3000 degrees Celsius, depending on the reduction temperature of the selected metal compound, and the heat refining time is between 60 seconds and 20 hours.
[0094] Typically, biochar is produced by heat treating or "pyrolyzing" biomass starting materials, such as wood chips, sawdust, forestry waste or any raw material of plant origin, at a temperature between 200 and 1000 degrees Celsius under an inert atmosphere, such as nitrogen, for a period of time between a few seconds ("fast" pyrolysis) and a few hours. Alternatively, hydrothermal heat treatment can be used to convert biomass into charcoal. Here, charcoal and water are placed in an autoclave at about 360 degrees Celsius and about 200 bar pressure for the same time as pyrolysis, and then dried. In all cases, the resulting charcoal mainly includes elemental carbon, wherein the so-called fixed carbon content is higher than at least 40%, but more usually at least 60%. The remainder includes a group of heteroatoms, mainly hydrogen, oxygen, nitrogen and sulfur. In addition, the charcoal may contain volatile substances, described as hydrocarbons, aliphatic hydrocarbons or aromatic hydrocarbons, which have a high enough molecular weight so that they will not evaporate during the thermal treatment. The exact composition will depend on the thermal treatment conditions and the selected biomass starting material. The resulting charcoal material is generally referred to as "green" charcoal. Any of the biochar materials described thus far may be selected for use in producing the compositions of matter described in this specification.
[0095] The metal compound insoluble in liquid can be any of countless possible metal compounds. The metal component of the compound is preferably a transition metal, such as but not limited to chromium, zirconium, molybdenum, ruthenium, rhodium, palladium, silver, cadmium, zinc, copper, nickel, cobalt, iron, manganese, chromium, vanadium or its arbitrary combination. However, the metal component can also include non-transition metals such as: sodium, magnesium, potassium, calcium, tin, lead, etc. Alternatively, the non-metallic part of the compound can be derived from using any inorganic or organic acid to generate salts, such as fluoride salts, chloride salts, sulfates, nitrates, phosphates, carbonates, etc. When heat treated, most organic and inorganic compounds will experience decomposition to form metal compounds, so these compounds can also be used indirectly. According to the selected starting metal compound, other intermediate compounds can also be formed.
[0096] In order to achieve uniform distribution during mixing and ensure minimum closed or inaccessible porosity, it is necessary to grind both biochar and metal compound separately or together. The grinding step is carried out using any conventional mill, such as ball mill, rod mill, gravel mill, bead mill, jet mill, planetary mill, vibrating mill, disc mill, grinding mill, air classification hammer mill, etc. The co-grinding of charcoal and metal compound achieves close contact, but it is difficult to control the particle size distribution achieved by each component. The biochar is ground to a particle size of less than about 800 microns, and more preferably less than about 500 microns. The metal compound is ground to a particle size of less than about 100 microns, and more preferably less than about 75 microns.
[0097] In general, there are several options for mixing biochar and metal compounds. If the metal compound is water-soluble, the compound can simply be dissolved in distilled or deionized water and the biochar soaked in this solution and then dried. Because the metal compound dissolves uniformly in the water, it is also uniformly distributed on the biochar after drying. However, in this case, it is difficult to control the relative amounts of char and metal compound. The maximum amount of metal compound that can be deposited is directly limited by the maximum solubility of the compound in a given liquid, which can be essentially constant over the available temperature range. In the case of water, for example, 0 to 100 degrees Celsius. Furthermore, it is actually very difficult to achieve uniform drying on uneven surfaces or porous particles, as is control over the particle size distribution achieved by the dried metal compound.
[0098] The two solids can be simply dry combined in a suitable solid mixer or combined by co-milling. This approach allows for direct control over the relative amounts of each component, but achieving uniform distribution is difficult when mixing the two solids. Biochar tends to be highly porous, with an irregular, grooved surface, making it difficult to evenly distribute the metal compound particles across the interior and exterior exposed surfaces. In addition, the metal compounds tend to agglomerate, resulting in particle sizes that are much larger than would otherwise be achieved during milling.
[0099] The third option combines existing methods by using a wet particulate slurry. In this case, two particulate, insoluble solids are placed in suspension using a suitable liquid medium, subsequently blended, and then the medium is optionally removed to obtain a dry mixture. This method allows the two components to be combined in a fixed ratio. In this way, the relative amounts of each component and their distribution can be precisely adjusted to obtain the exact set of final properties required for a specific application.
[0100] Furthermore, the use of a liquid slurry means that the metal compound is evenly distributed in the biochar and on all surfaces of the biochar. Typically, the medium or liquid is water and the mass ratio of the liquid to the other components is between 0.3 and 5. In order to ensure adequate wettability, even distribution of the individual particles and retention of the distribution after drying, it is necessary to use an additive formulation for one or both particle slurries. The additive formulation includes a mixture of multifunctional components including at least one or a combination of the following: surfactants, binders, dispersants, rheology modifiers, wetting agents, anti-foaming agents and any combination thereof.
[0101] Depending on the selected insoluble metal compound and the source of the biochar, the selection and relative amounts of each component in the additive formulation may need to vary to achieve optimal distribution when undergoing the desired processing steps. For example, the selected metal compound may tend to agglomerate, in which case a suitable liquid-solid surfactant will be required, in other cases the biochar or metal compound will not be easily wetted by the liquid, in which case a wetting agent must be added to achieve a uniform slurry mixture. In some processes, it may be necessary to pump the slurry from one container to another, in which case a rheology modifier may be required to achieve the appropriate viscosity, in other cases the selected liquid may cause foaming during the slurry mixing process, so an anti-foaming agent will be required.
[0102] The components of the additive formulation may be selected from one or more of the following: AEROSOL C-61, AG 6202, ALCOSPERSE175, ALMIPAL P, Aminoethylethanolamine, ammonium fluoride, AMMONYX M, Aquatreat BW30, Arkopal, Armid O. Aziridine, Polyisocyanate, Bronidox, BTBAB-90, BTBAC-50, Bteac-50, BTMAC-50, BTMAH-40, Styrene-butadiene binder, Styrene-butadiene binder, butyl stearate, calcium stearate, Dodecanedioic acid, ENORDET, Ethoduomeen T / 25, EURAMAAT, EUR-AMID, EURANAAT, EURASOL, EUROGLYC, EUROQUAT, EUROWET, EUROXIDE, EXOdis PC30, FOAMASTER MO 2133, Heliogen Blue D 7079, Lauryl alcohol, Lipal MSC, Lipal NTD, Magna MERPOL SE, NANSA, Oleamid, Oleic acid, Pasatell M-182 (2-798), PEG-400, Pentaerythritol oleate, POIZ 520, POIZ 530, Polyamide, Polyester, POLYFON H, Polyethylene glycol, Polymerizable additives, potassium soybean oleate, Quickpearl PK3, REWOCID DU185SE, Rewopol SB L 203, ROKAmer 1010 / 50, SDS, Sico50BC, Sidos 70, sodium dodecylbenzene sulfonate, sodium N-hexadecanoyl-L-alanine, sodium silicate, sorbitan monooleate, sorbitan monopalmitate, Steamcare B12, stearyl chloride, SugaDetAPG-10, Sulfoccinate LSS, Sulfated Butyl Oleate, SURFACARE OACID, TBAH-40, TBAHS-50, DDM, TLMAC-30, TMAC-100ARQUAD 41-100, Tomamine Amphoteric 12, Triethanolamine, Triethylbenzylammonium chloride, Tween 80, UFACID K, YB-0100, YB-150, YB-191, YB-2000, YB-904, YBASD-200, or a combination thereof.
[0103] Thus, after mixing and pre-drying (if necessary), a blended composite of biochar, metal compound and additive formulation is obtained. When this mixture is heat treated at temperatures between 400 and 3000 degrees in order to produce graphite, several important changes occur. The residual liquid is removed, and almost all residual heteroatoms and volatile matter present in the biochar are removed, thereby producing a material that is almost entirely carbon and has a fixed carbon content of more than ~99%. This material is generally referred to as "calcined" or "completely carbonized" biochar. The amount of fully carbonized biochar is approximately equal to the fixed carbon content of the original biochar. At high temperatures above 400 degrees Celsius, in the presence of carbon such as biochar, the metal compound or any intermediate compound formed will be reduced to their metallic state. Reduction is usually achieved under an inert atmosphere and consumes some biochar. Therefore, during the thermal treatment, the char is carbonized to pure carbon and the metal compound is reduced to a pure metal or alloy.
[0104] Since additives are most often long-chain polymers, they will degrade when heated above several hundred degrees Celsius. This will be accompanied by a significant loss of mass, as gaseous decomposition products are formed. In some cases, lighter elements or compounds present will also evaporate or sublime, depending on the final temperature. Furthermore, since the additive formulation usually accounts for less than 5 wt% of the initial mixture before heat treatment, the residual additive formulation after heat treatment is negligible.
[0105] All of the metal compounds described above have different elemental compositions, however, since all of the metal compounds are reduced to their metallic state during the heat treatment step, it is convenient to only refer to the metal content associated with the heat treated material. In addition, since the biochar is carbonized to approximately 99 wt% carbon during the heat treatment step, the composition of the heat treated mixture can be simplified as a binary mixture of metal and carbon. Therefore, for convenience, the carbon in the binary mixture is described as the fixed carbon in the biochar portion of the mixture, while the metal in the binary mixture is described as the metal portion of the metal compound present in the mixture.
[0106] A catalytic conversion process occurs when an elemental metal is exposed to a carbon source such as charcoal under inert conditions at temperatures between about 400 and about 3000 degrees Celsius. Thus, over time, amorphous charcoal is converted to highly crystalline graphite. This converts one allotrope of pure carbon into another. The extent and rate of graphite formation is highly dependent on the metal chosen, but is relatively insensitive to the initial choice of biomass, primarily because it is already carbonized. The exact mechanism of the catalytic conversion remains unknown, but two possible theories have been proposed, namely dissolution-precipitation and carbide formation-decomposition. In the former, the carbon source dissolves in the metal and graphite spontaneously precipitates due to differences in its free energy or degree of structural order. In the latter, unstable metal carbides are formed, which spontaneously decompose to produce graphite. The exact formation mechanism is not relevant to the current disclosure.
[0107] Depending on the selected biochar, metal compound, liquid and additive formulation, different amounts of charcoal will be converted into graphite. The characteristics of the resulting graphite will largely depend on the selected biochar, metal compound, liquid and additive formulation. However, it has been demonstrated that the key factor determining the achieved conversion rate is the relative percentage of carbon and metal, previously referred to as the binary mixture after thermal treatment. Depending on the catalytic effect of the metal, the higher the percentage of metal, the higher the expected conversion rate. In order to achieve an economical and efficient process, the conversion rate should be as high as possible without using excess metal compound. In order to achieve this efficiency, control of the particle size and distribution of the metal compound particles is crucial.
[0108] The second key characteristic of the resulting graphite is its specific surface area (SSA). This characteristic is a composite result of the uniformity of distribution of the metal compounds obtained in the mixture and the actual particle size distribution. Smaller particles will tend to form smaller graphite crystals with low crystallinity, which leads to a higher specific surface area, and conversely, larger particles will produce large crystals with high crystallinity and lower specific surface area. In general, impregnation with a solution in which solids are dissolved will result in a small particle size distribution after drying, as the concentration is limited. On the other hand, solid-solid dry mixing under high loads tends to produce large particle sizes due to agglomeration effects.
[0109] Although the metal compound can have countless different compositions, and the biochar can have a wide range of fixed and volatile carbon, depending on the pyrolysis conditions and temperature, the important ratio in terms of conversion efficiency is the ratio of the metal present in the metal compound to the fixed carbon present in the char. Typically, a metal to carbon mass ratio of about 0.25 to about 2.03 is used.
[0110] Based on these considerations, the overall composition of matter can be defined as a mixture comprising biochar, a metal compound, a liquid, and an additive formulation, wherein the mixture comprises (a) between about 1 and about 90 weight percent biochar, (b) between about 2 and about 90 weight percent metal compound, (c) between about 0.001 and about 83 weight percent liquid, and (d) between about 0.001 and about 5 weight percent additive formulation. Any weight percentages of the four components can be selected from these specified ranges as long as the sum totals to 100%.
[0111] To describe the exact composition in more detail, a particular metal compound and fixed carbon of the charcoal may be selected. To simplify the range specification, the liquid composition has been omitted, limiting the number of compositions to three. Without limitation, the iron oxide may be used in combination with a charcoal having 70% fixed carbon to obtain a dry mixture. Conveniently, the percentage of metal present in the iron oxide is about 70%, the same as the fixed carbon of the selected charcoal. In this case, the effects cancel out and the previously described binary composition (mass ratio of metal to carbon) is directly interpreted as the desired metal compound and charcoal mixture composition (on a dry wt / wt basis). That is, the desired composition of the charcoal combined with the metal compound is from about 10 to about 80 wt% of the metal compound, more preferably from about 20 to about 67 wt% of the metal compound, with the charcoal making up the difference.
[0112] Based on the fixed percentage of additives in the overall composition (on a dry wt / wt basis), the impact of additional additive formulations can be easily calculated. The desired surfactant percentage is described as 0.001% up to about 5wt% (on a dry wt / wt basis) of the final mixture. Due to the low concentration of the additional component, it has a relatively small impact on the composition of the overall mixture. For the case of iron oxide, the material composition of the desired mixture (on a dry wt / wt basis) can be described as a metal compound between about 9.5 and about 80wt%, an additive formulation between about 0.001 and about 5wt%, and the difference is made up by carbon. More preferably, the desired material composition (on a dry wt / wt basis) can be described as a metal compound between about 19 and about 67wt%, an additive formulation between about 0.001 and about 5wt%, and the difference is made up by carbon. The range of metal compounds and carbon is specified at the minimum surfactant concentration, which leads to the widest range of these components.
[0113] Taking into account other potential choices in metal compounds, a general range of material compositions can be specified for the mixture (on a dry wt / wt basis) by slightly increasing the two sets of ranges, namely the base and preferred ranges. In this case, the mixture (on a dry wt / wt basis) has (a) a metal compound content between about 9.5 and about 90 weight percent, (b) an additive formulation component between about 0.001 and about 5 weight percent, and (c) biochar between about 90 and about 5 weight percent to make up the difference. More preferably, the mixture (on a dry wt / wt basis) has (a) a metal compound content between about 19 and about 82 weight percent, (b) an additive formulation component between about 0.001 and about 5 weight percent, and (c) biochar between about 81 and about 13 weight percent to make up the difference. The ranges for metal compounds and charcoal are specified at the minimum surfactant concentration, which results in the widest range for these components.
[0114] The expected results of different mixing methods based on the particle size obtained are summarized in Table 2.
[0115] Table 2: Expected results
[0116] Hybrid Approach Metal content Particle distribution Conversion rate SSA Wet solution Low good Low high Dry solid high Difference high Low wet slurry medium Fair medium medium
[0117] The results actually observed are summarized in Table 3, as detailed in Examples 1 to 3.
[0118] Table 3: Observed results
[0119]
[0120] The wet solution process surprisingly achieves high conversion to graphite despite only low metal to carbon ratios being achieved. The higher than expected conversion is believed to be due to the increased mobility of small metal particles relative to larger particles generated during dry mixing. In contrast, dry solid mixing achieves only moderate levels of conversion despite achieving higher catalyst loadings. Most surprisingly, the good distribution of finely milled metal compound particles achieved during wet slurry mixing enables the simultaneous achievement of materials with high conversion and low surface area. This is unexpected based on previous observations of wet solution and dry mixing situations, where one performance is traded off against another, and therefore both performances are expected to be partially compromised. In contrast, the use of additive formulations in combination with particulate material slurries produces an optimized system that maximizes conversion to preferred low specific surface area products. In addition, the properties of the material can be fine-tuned in a unique way by directly controlling the relative size and amount. This is not possible for dissolved metal compounds because they are limited by their maximum solubility in a given liquid and lack particle size control. Thus, using the present composition of matter, a size range between finely distributed incorporation of wet solutions to coarse particles of dry solid mixes can be achieved.
[0121] Example
[0122] The embodiments described herein are provided for the purpose of illustrating specific embodiments of the present invention and are not intended to limit the present invention in any way. Although the embodiments described herein have been used to describe a method, it should be understood that such details are only for this purpose, and those skilled in the art can change them without departing from the spirit and scope of the whole process.
[0123] The microwave laboratory setup used to produce one of the samples can be described as follows. The samples were heated to temperatures of up to 2000°C using a specially designed microwave heater with a maximum power input of 3 kW. Figure 1 The layout of the heater is shown. A microwave generator provides power to the heater via a WR340 waveguide autotuner, PTFE windows and passive coupling elements. The microwave generator is a 2.45 GHz YJ1600 based source (Sairem). The sample is placed in a crucible and positioned within the heater at a predetermined height, usually on a "pillar" or stand to obtain a specific radiation distribution (see Figure 2a). The apparatus is sealed and purged with nitrogen (99.9% purity) at a high flow rate for about 1 hour to establish an inert atmosphere, and then a lower purge flow rate is used to maintain the atmosphere. Thereafter, power is gradually applied at a rate of 30 W / min to slowly heat the sample and quickly reach a steady state at the desired final power. A stable power setting is selected to achieve the desired temperature. The final power level is then maintained for a specific time, depending on the desired result. At this point, the sample emits a red glow and the crucible surface temperature can be measured through a sight glass using a handheld pyrometer, such as Figure 2 The pyrometer readings showed a high level of fluctuation and uncertainty, so the temperature bands are reported. The power was then kept stable for a given time frame, after which the generator was turned off and the resulting mixture sample was allowed to cool for removal. Alternatively, a conventional electrically heated furnace equipped with a pyrometer was used to generate the remaining samples.
[0124] To evaluate the conversion of biochar to graphite, the analytical technique of X-ray diffraction (XRD) was used. A fitting procedure was applied to the obtained XRD pattern or spectrum based on the expected composition of the mixture. Theoretical hexagonal and rhombic graphite cells were simulated using the Rietveld procedure. Amorphous carbon was modeled using a scaled lampblack reference pattern. In this way, the relative amounts of residual amorphous carbon and formed crystalline carbon can be inferred in order to calculate the conversion of one to the other.
[0125] Example 1
[0126] Sawdust (50 g) from pine (pinus radiata) was hydrothermally treated in an autoclave with deionized water at a temperature of about 360 degrees Celsius for 20 min. The sample was allowed to cool and then filtered using a Buchner funnel; the resulting charcoal was dried in a conventional oven. Dry charcoal (10.1 g) having a carbon content of about 80% was wet impregnated with a solution of 8.2 g of manganese acetate (tetrahydrate) in 16 ml of water. The resulting mixture was placed in a crucible and dried in a conventional tray oven before being transferred to a microwave heater. Inert conditions were established and the power was gradually increased at a rate of about 30 W / min up to 1.3 kW. The temperature was measured to be between about 1400-1600 degrees Celsius. The power was kept stable for about 5 to 10 minutes before being disconnected. Once cooled, the sample was sieved to less than 1 mm and then leached overnight with 500 ml of hydrochloric acid, followed by washing with deionized water and filtering with a Buchner funnel. The resulting graphite was analyzed using XRD (Bruker D8 Advance diffractometer, using a 1 mm high parallel beam of cobalt Kα radiation from a mirror, weighted average wavelength 1.709026 angstroms) and BET surface area analysis. The XRD spectrum is shown in Figure 3The d-spacing was 0.3380 nm from the 002 peak position and the crystallinity was 93.0%. The spectrum was analyzed using the program and 90.9% of the biochar was converted into graphite. The sample was also found to have a 74.0 m 2 For this sample, the binary composition of the mixture after heat treatment can be expressed as:
[0127] (a) a carbon content of about 79 weight percent,
[0128] (b) a metal content of about 21 weight percent.
[0129] For this sample, the composition of matter (on a dry wt / wt basis) can be expressed as:
[0130] (a) a biochar content of about 63.6 weight percent,
[0131] (b) a metal compound content of about 36.4 weight percent.
[0132] Example 2
[0133] Pyrolysis hardwood charcoal (~14g) obtained from "Solid Energy" in New Zealand was ground and sieved to less than 200 microns. Carbon with a carbon content of about 70% was combined with about 21g of iron oxide using dry mixing. The resulting mixture was placed in a crucible and heated in a conventional electrically heated furnace (RD WEBB air-cooled vacuum furnace model RD-G). Inert conditions were established by purging with argon (>99.9%), and the temperature was increased at a ramp rate of 10 degrees per minute. The final temperature was set at 1750 degrees Celsius. The temperature remained stable for 180 minutes, after which the furnace was turned off. Once cooled, the sample was sieved to less than 1mm, then leached overnight with 500ml of hydrochloric acid, followed by washing with deionized water and filtering with a Buchner funnel. The resulting graphite was analyzed using XRD (Bruker D8 Advance diffractometer, using a 1mm high parallel beam of cobalt Kα radiation from a mirror, weighted average wavelength 1.709026 angstroms) and BET surface area analysis. The XRD spectrum is shown in Figure 4 The d-spacing was 0.3368 nm from the 002 peak position and the crystallinity was 96.1%. The spectrum was analyzed using the program and 60.9% of the biochar was calculated to be converted into graphite. The sample was also found to have a 1.21 m 2 For this sample, the binary composition of the mixture after heat treatment can be expressed as:
[0134] (a) a carbon content of about 40 weight percent,
[0135] (b) a metal content of about 60 weight percent.
[0136] For this sample, the composition of matter (on a dry wt / wt basis) can be expressed as:
[0137] (a) a biochar content of about 40 weight percent,
[0138] (b) about 60 weight percent metal oxide content.
[0139] Example 3
[0140] Pyrolysis hardwood charcoal (~9.8g) obtained from "Solid Energy" in New Zealand was ground and sieved to less than 500 microns. Carbon with a carbon content of about 70% was combined with about 15.1g of iron oxide using wet mixing. First, the charcoal was combined with water (16ml) and a surfactant: a mixture of 75wt% water and 25wt% ethanol (0.12ml). The catalyst was then combined with water (16ml) and a surfactant: a mixture of 80wt% water and 20wt% sodium dodecylbenzene sulfonate (0.55ml). The two suspensions were mechanically stirred and homogenized using a blade mixer and an ultrasonic horn. The two suspensions were then mixed, followed by mechanical stirring and homogenization. Subsequently, the product was placed in a conventional tray oven for drying. The resulting powder was placed in a crucible and heated in a conventional electrically heated furnace (RD WEBB air-cooled vacuum furnace model RD-G). Inert conditions were established by purging with argon (>99.9%) and the temperature was increased at a ramp rate of 10 degrees per minute. The final temperature was set at 1445 degrees Celsius. The temperature was kept stable for 135 minutes, after which the furnace was turned off. Once cooled, the sample was sieved to less than 1 mm and then leached overnight with 500 ml of hydrochloric acid, followed by washing with deionized water and filtering with a Buchner funnel. The resulting graphite was analyzed using XRD (Bruker D8 Advance diffractometer, using a 1 mm high parallel beam of cobalt Kα radiation from a mirror, weighted average wavelength 1.709026 angstroms) and BET surface area analysis. The XRD spectrum is shown in Figure 5 The d-spacing was 0.3370 nm from the 002 peak position and the crystallinity was 95.7%. The spectrum was analyzed using the program and 98.2% of the biochar was converted into graphite. The sample was also found to have a 1.98 m 2 For this sample, the binary composition of the mixture after heat treatment can be expressed as:
[0141] (a) a carbon content of about 39 weight percent,
[0142] (b) A metal content of about 61 weight percent.
[0143] For this sample, the composition of matter (on a dry wt / wt basis) can be expressed as:
[0144] (a) a biochar content of about 38.5 weight percent,
[0145] (b) a metal oxide content of about 59.3 weight percent,
[0146] (c) about 2.1 weight percent of the additive formulation content.
[0147] Figure 6 An outline of the overall process followed in Example 3 is shown. Biomass (1) is converted into biochar in particle form (2). The biochar is then milled (3) and combined with an additive formulation to form a slurry. Metal oxides in particle form are milled (3) and combined with an additive formulation to form a slurry. The two slurries are then combined to form a composition of matter (4), optionally followed by drying. The composition of the mixture represented by biochar, metal oxide, liquid and additive (4) is critical to the ability to form graphite with desired properties at a desired conversion rate (5) during thermal treatment.
[0148] References
[0149] [1]Franklin, RE, 1951. Crystallite growth in graphitizing and non-graphitizing carbons. Proceedings of the Royal Society of London. Series A. Mathematical and Physical Sciences, 209(1097), pp.196-218.
Claims
1. A composition of matter comprising a mixture of biochar, a metal compound, a liquid and an additive formulation, wherein: The mixture includes (a) between about 1 and about 90 weight percent of biochar, (b) between about 2 and about 90 weight percent of a metal compound, (c) between about 0.001 and about 83 weight percent of a liquid, and (d) between about 0.001 and about 5 weight percent of an additive formulation, wherein the additive formulation is selected from one or more of the following: a surfactant, a binder, a dispersant, a rheology modifier, a wetting agent, an anti-foaming agent, or any combination thereof.
2. The composition according to claim 1, wherein The liquid and metal compound are selected to ensure that the solubility of the metal compound in the liquid is minimized when the composition is used.
3. The composition according to claim 1 or claim 2, wherein The liquid is water.
4. The composition according to any one of claims 1 to 3, wherein The metal compound includes a transition metal.
5. The composition according to claim 4, wherein The transition metal is selected from chromium, zirconium, molybdenum, ruthenium, rhodium, palladium, silver, cadmium, zinc, copper, nickel, cobalt, iron, manganese, chromium, vanadium or any combination thereof.
6. The composition according to any one of claims 1 to 5, wherein The metal compounds are derived from the thermal decomposition of organic or inorganic metal salts.
7. The composition according to any one of claims 1 to 6, wherein On a dry wt / wt basis (excluding the liquid), the mixture includes (a) between about 9.5 and about 90 weight percent of the metal compound, (b) between about 0.001 and about 5 weight percent of the additive formulation, and (c) between about 5 and about 90.5 weight percent of the biochar.
8. The composition according to claim 7, wherein On a dry wt / wt basis (excluding the liquid), the mixture more preferably includes (a) between about 19 and about 82 weight percent of the metal compound, (b) between about 0.001 and about 5 weight percent of the additive formulation, and (c) between about 13 and about 81 weight percent of the biochar.
9. The composition according to any one of claims 1 to 8, wherein The metal compound is a transition metal oxide.
10. The composition according to claim 9, wherein The transition metal oxide is selected from oxides of iron, copper, nickel, manganese, vanadium, tin, chromium, zinc, titanium and cobalt or any combination thereof.
11. The composition according to claim 10, wherein The transition metal oxide includes iron oxide.
12. The composition according to any one of claims 1 to 11, wherein The mixture comprises, on a dry wt / wt basis, (a) between about 9.5 and about 80 weight percent iron oxide, (b) between about 0.001 and about 5 weight percent additive formulation, and (c) between about 20 and about 90.5 weight percent biochar, wherein the biochar has a fixed carbon content of approximately 70%.
13. The composition according to claim 12, wherein The mixture (on a dry wt / wt basis) more preferably includes (a) between about 19 and about 67 weight percent iron oxide, (b) between about 0.001 and about 5 weight percent additive formulation, and (c) between about 33 and about 81 weight percent biochar, wherein the biochar has a fixed carbon content of at least 70%.
14. The composition according to any one of claims 1 to 13, wherein The biochar is produced by thermally treating woody biomass.
15. The composition according to any one of claims 1 to 14, wherein The biochar in the mixture is in particulate form.
16. The composition according to claim 15, wherein The biochar has an initial particle size of less than about 50 mm.
17. The composition according to any one of claims 1 to 16, wherein The metal compound in the mixture is in particulate form.
18. The composition according to any one of claims 1 to 17, wherein The metal compounds and biochar are both in particulate form.
19. The composition according to claim 17 or claim 18, wherein The metal compound has a primary particle size of less than about 5 mm.
20. The composition according to any one of claims 1 to 19, wherein The biochar has a primary particle size of less than about 50 mm, and the metal compound has a primary particle size of less than about 5 mm.
21. A composition according to any one of claims 15 to 20, wherein The biochar has a particle size of less than about 800 microns.
22. The composition according to claim 21, wherein The biochar has a particle size of less than about 500 microns.
23. A composition according to any one of claims 21 to 22, wherein The metal compound has a particle size of less than about 100 microns.
24. The composition according to claim 23, wherein The metal compound has a particle size of less than about 75 microns.
25. A composition according to any one of claims 1 to 24, wherein The additive formulation includes two or more of a surfactant, a binder, a dispersant, a rheology modifier, a wetting agent, an anti-foaming agent, or any combination thereof.
26. The composition according to claim 25, wherein The additive formulation includes one or more additives selected from one or more of the following: AEROSOL C-61, AG 6202, ALCOSPERSE 175, ALMIPAL P, Aminoethylethanolamine, ammonium fluoride, AMMONYX M, Aquatreat BW30, Arkopal, Armid O. Aziridine, Polyisocyanate, Bronidox, BTBAB-90, BTBAC-50, Bteac-50, BTMAC-50, BTMAH-40, Styrene-butadiene binder, Styrene-butadiene binder, butyl stearate, calcium stearate, Dodecanedioic acid, ENORDET, Ethoduomeen T / 25, EURAMAAT, EUR-AMID, EURANAAT, EURASOL, EUROGLYC, EUROQUAT, EUROWET, EUROXIDE, EXOdis PC30, FOAMASTER MO 2133、 Heliogen Blue D 7079、 Lauryl alcohol, Lipal MSC, Lipal NTD, Magna MERPOL SE, NANSA, Oleamid, Oleic acid, Pasatell M-182 (2-798), PEG-400, Pentaerythritol oleate, POIZ 520, POIZ 530, Polyamide, Polyester, POLYFON H, Polyethylene glycol, Polymerizable additives, potassium soybean oleate, Quickpearl PK3, REWOCID DU185SE, Rewopol SB L 203, ROKAmer 1010 / 50, SDS, Sico 50BC, Sidos 70, sodium dodecylbenzene sulfonate, sodium N-hexadecanoyl-L-alanine, sodium silicate, sorbitan monooleate, sorbitan monopalmitate, Steamcare B12, stearyl chloride, SugaDet APG-10, Sulfoccinate LSS, Sulfated Butyl Oleate, SURFACARE O ACID、TBAH-40、TBAHS-50、 DDM, TLMAC-30, TMAC-100ARQUAD 41-100, Tomamine Amphoteric 12, Triethanolamine, Triethylbenzylammonium chloride, Tween 80, UFACID K, YB-0100, YB-150, YB-191, YB-2000, YB-904, YBASD-200, or any combination thereof.
27. A method of heat treating a composition as defined in any one of claims 1 to 26 to a temperature above the reduction temperature of the metal compound, thereby reducing it to an elemental metal or alloy.
28. The method according to claim 27, wherein: The thermal treatment results in the conversion of amorphous biochar into crystalline graphite.
29. A method according to claim 27 or claim 28, wherein: The conversion rate of amorphous carbon formed by the heat treatment of the mixture to crystalline graphite is greater than about 50%.
30. The method of claim 29, wherein: The conversion to graphite is greater than about 75%.
31. The method according to any one of claims 27 to 30, wherein: The crystalline graphite formed by the heat treatment of the mixture has a crystallinity greater than about 90%.
32. The method according to claim 31, wherein: The crystallinity of the crystalline graphite is greater than about 95%.
33. The method according to any one of claims 27 to 32, wherein: The specific surface area of the graphite formed by the heat treatment of the above defined composition of matter is less than about 50 m2 / g.
34. The method of claim 33, wherein: The specific surface area of the graphite is less than about 30 m2 / g.
35. A method for producing a composition as described in any one of claims 1 to 26, comprising the steps of: i) thermally treating the biomass in particle form at a temperature of about 200 to about 1000 degrees Celsius under inert conditions to form a particle biochar; ii) grinding the biochar to obtain a particle size of less than about 800 microns, more preferably less than 500 microns; iii) milling a suitable metal compound to obtain a particle size of less than about 100 microns, more preferably less than 75 microns: iv) combining the obtained biochar with the metal compound, liquid and additive formulation; and v) heating the mixture to about 400 to about 3000 degrees Celsius under inert conditions to produce graphite carbon.
36. The method of claim 35, wherein: The biomass is thermally treated in water in a hydrothermal step to produce the biochar.
37. The method of claim 35, wherein: The biomass is thermally treated under inert conditions in a dry pyrolysis step to produce the biochar.
38. A method according to any one of claims 35 to 37, wherein: The biomass is forestry residue.
39. The method of claim 38, wherein: The forestry residue is sawdust.
40. The method according to any one of claims 35 to 37, wherein: The biomass is lignocellulosic biomass or a lignin derivative.
41. The method according to any one of claims 35 to 40, wherein: The biomass is wood chips or any other wood based material.
42. The method according to any one of claims 35 to 41, wherein: The liquid is water.
43. The method according to any one of claims 35 to 42, wherein: The liquid and metal compound are selected to ensure that, when used, the solubility of the metal compound in the liquid is minimal.
44. A method according to any one of claims 35 to 43, wherein: In step iv), the metal compound is combined with the biochar by wet blending together with an additive formulation in a mixer.
45. The method according to any one of claims 35 to 44, wherein: In step iv), the metal compound is combined with the biochar by wet grinding in a mill together with an additive preparation.
46. The method according to any one of claims 35 to 45, wherein: The additive formulation for the mixed slurry includes two or more of the following: a surfactant, a binder, a dispersant, a rheology modifier, a wetting agent, an anti-foaming agent, and any combination thereof.
47. A method according to any one of claims 35 to 44, wherein: In step iv), the metal compound in water is combined with an additive formulation to produce a particulate metal compound slurry by using a mixer to form a particulate slurry in water.
48. The method according to any one of claims 35 to 44 and 47, wherein In step iv), the biochar in water is combined with an additive formulation to produce a slurry of particulate biochar by using a mixer to form a slurry of particulates in water.
49. A method according to claim 47 or claim 48, wherein: The additive formulation is selected from the group consisting of: a binder, a dispersant, a rheology modifier, a wetting agent, an anti-foaming agent, and any combination thereof.
50. The method according to any one of claims 47 to 49, wherein: The particulate metal compound slurry is combined with the particulate biochar slurry and then blended together in a mixer.
51. A method according to any one of claims 35 to 50, wherein: The mixture obtained in step (iv) is heated in step (v) to about 400 to about 3000 degrees Celsius using a controlled atmosphere oven, furnace or other heating device under inert conditions to produce graphite carbon, provided that the heat treatment temperature must be above the reduction temperature of the selected metal compound to ensure that it is reduced to the elemental metal or alloy state.
52. A method according to any one of claims 35 to 51, wherein: The metal compound is a transition metal oxide.
53. The method of claim 52, wherein: The transition metal oxide is selected from oxides of iron, copper, nickel, manganese, vanadium, tin, chromium, zinc, titanium and cobalt or any combination thereof.
54. The composition according to claim 53, wherein The transition metal oxide includes iron oxide.